Outsourcing a company's warehousing function to 3rd party logistics service provider (3PL) - Sim, Maggie Lye Hong. (2008)
The objective of this dissertation is to develop basis for the strategic and tactical planning of outsourcing. It is useful for organizations that may need to undertake outsourcing activities, as opposed to firms that provide them.